Signal detection for bleeding associated with the use of direct oral anticoagulants. (1st July 2018) - Nathan, Kobi T.; Conn, Kelly M.; van Manen, Robbert P.; Brown, Jack E.
Abstract : Purpose: The potential link between serious or life-threatening bleeding and the use of direct oral anticoagulants (DOACs) was evaluated. Methods: Qualitative and quantitative reviews of case reports of bleeding events involving dabigatran, rivaroxaban, apixaban, edoxaban, and warfarin through March 31, 2017, were performed. A disproportionality analysis was conducted for each DOAC using an empirical Bayesian approach based on the relative reporting rate. Subanalyses were performed to assess (1) bleeding events (including mortality and life-threatening events) associated with DOACs among all adverse-event reports and (2) warfarin-related bleeding events. These analyses were conducted based on clinical definitions from the Medical Dictionary for Regulatory Activities. Results: During the Food and Drug Administration Adverse Event Reporting System (FAERS) review period, 35 adverse-event terms (in any system organ class) with a disproportionality score (EB05 ) of >7.5 for DOACs were identified; this accounted for 40, 109 adverse-event reports. Adverse events with the highest disproportionality scores included atrial thrombosis, increased factor X level, dysfunctional uterine bleeding, high-frequency ablation, pericardial hemorrhage, and internal hemorrhage. Adverse events with the highest EB05 (>5) included internal hemorrhage, hemorrhage, and exsanguination; events with the greatest number of patient experiences included hemorrhage (6, 881 events), internal hemorrhage (2, 569 events), and hematoma (1, 995 events). Warfarin-related events (including death or life-threatening events) were also assessed. A total of 8, 729 adverse events were associated with warfarin use. The most common of these included hemorrhage (6, 225 events), hematoma (2, 199 events), and internal hemorrhage (270 events). Conclusion: The disproportionality analysis of the FAERS database suggests a quantitative signal between DOAC use and life-threatening or serious bleeding.